Childfree Dalam Pandangan Katolik: Pandangan Penganut, Pemuka Agama, dan Umat Gereja - Kristy, Bella (Universitas Muslim Maros, 2024)
The term childfree is used to refer to people or couples who choose not having children. Childfree is considered violating Catholic marriage vow and becomes controversy. Despite its controversy, childfree becomes more common. This article deals with childfree in Catholic teachings from the view of childfree adherents, religious leaders, and church people. This qualitative research was conducted in Makassar. There are 13 informants who get involved in this study, consisting of six childfree adherents, a priest, two fraters and four Catholics. Data was collected using in-depth interview and observation. Childfree among Catholic couples raises oppositional responses, between those who agree and those who disagree. The Catholic Church teaches that procreation is the main purpose of marriage, while each individual is free to choose not to have children (childfree). Procreation is not only seen as a biological act, but also as a spiritual act that consummates marriage and is part of God's plan. Children are not only considered descendants, but also